2017
DOI: 10.1177/1352458517728342
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval exercise improves cognitive performance and reduces matrix metalloproteinases-2 serum levels in persons with multiple sclerosis: A randomized controlled trial

Abstract: HIT represents a promising strategy to improve verbal memory and physical fitness in persons with MS. Further research is needed to determine the impact of exercise on biomarkers in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
123
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 34 publications
12
123
0
10
Order By: Relevance
“…But is verbal learning and memory the neurocognitive domain most sensitive to exercise interventions? Consistent with our earlier study in progressive MS, a recent trial on high intensity training could show effects on different cognitive dimensions with strongest effects in the verbal memory dimension of the BICAMS (Zimmer et al 2017). However, in the few other MS exercise studies most effects were reported in information processing speed and executive functioning (Sandroff et al 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…But is verbal learning and memory the neurocognitive domain most sensitive to exercise interventions? Consistent with our earlier study in progressive MS, a recent trial on high intensity training could show effects on different cognitive dimensions with strongest effects in the verbal memory dimension of the BICAMS (Zimmer et al 2017). However, in the few other MS exercise studies most effects were reported in information processing speed and executive functioning (Sandroff et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, the study did not show effects on any cognitive measure and failed to produce significant changes in any of the obtained patient related or objective outcome measures for functioning in MS. These results thus cast doubt on the generalizability of recent trials that suggested the potential of exercise to improve cognitive function in progressive (Briken et al 2014) or relapsing-remitting MS (Zimmer et al 2017).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, sphingosine-1-phosphat (S1P) -a sphingolipid metabolite known to modulate the CNS directly (Hla and Brinkmann, 2011;Soliven et al, 2011) or indirectly by facilitating BDNF expression (Fukumoto et al, 2014;Smith et al, 2018) -may also be involved in mediating exercise-induced neuroprotective effects in pwMS. Indeed, AT alone (Bansi et al, 2013;Briken et al, 2016;Castellano and White, 2008;Gold et al, 2003) or combined with pilates (Ozkul et al, 2018) or RT (Wens et al, 2016) can lead to acute and chronic increases in circulating BDNF levels in pwMS, although negative findings also exist (Bansi et al, 2013;Briken et al, 2016;Schulz et al, 2004;Zimmer et al, 2017). While little is known about circulating S1P levels in pwMS, AT has been shown to increase acute (Baranowski et al, 2015;Baranowski et al, 2011) and chronic circulating S1P levels in healthy young individuals (Ksiazek et al, 2018).…”
Section: A N U S C R I P T Introductionmentioning
confidence: 99%
“…Exercise can be a helpful rehabilitation approach for individuals with MS to reestablish function, endorse wellness, and increase involvement in activities of daily living [11,12,13]. Moreover, accumulating evidence suggests that persons with MS are less physically active than are non-diseased populations [12].…”
Section: Introductionmentioning
confidence: 99%